Mengamalkan Nilai-Nilai Pancasila ke Dalam Pendidikan di Tengah Pandemi Covid-19 - Isfi Aulia; Dinie Anggraeni Dewi (STKIP PGRI SITUBONDO, 2021)
Pancasila is the ideology of the Indonesian nation which is the guideline or basis for regulating the life of all Indonesian people, especially in the field of education. The writing of this article uses a qualitative method, which is a research using available theory and data. The sources cited in this theory are journals, articles and theses. This study aims to find out how to practice the values ​​contained in Pancasila in education in the midst of a Covid-19 pandemic like this. The writing of this article is to use a qualitative research method or a descriptive approach. In this study, the results show that in Pancasila, there are five principles, each of which provides benefits to the Indonesian people, especially their practice in the field of education during the Covid-19 pandemic like this. Education must continue to run even in these circumstances. Education is a powerful weapon to change the world, achieve the aspirations of the nation and be able to educate all generations of the Indonesian nation.